13+27=-4(2x-10)

Simple and best practice solution for 13+27=-4(2x-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13+27=-4(2x-10) equation:



13+27=-4(2x-10)
We move all terms to the left:
13+27-(-4(2x-10))=0
We add all the numbers together, and all the variables
-(-4(2x-10))+40=0
We calculate terms in parentheses: -(-4(2x-10)), so:
-4(2x-10)
We multiply parentheses
-8x+40
Back to the equation:
-(-8x+40)
We get rid of parentheses
8x-40+40=0
We add all the numbers together, and all the variables
8x=0
x=0/8
x=0

See similar equations:

| 7(-2+2x)=42 | | 2x-12=-5x-26 | | -1=m+10 | | x2+4x-16x=2 | | 180=7x-3(15-6x) | | 17+9(5)=8+3(4x)-6x | | m4m=0.6 | | 3x–7=11 | | -4(-10+3x)=40 | | (3x+3)=(4x-8) | | 6b+6b-9=5+10b | | 4x+2.6=8.1+3x | | h=1.5(12)+3 | | 2+4x=2x+26 | | 2(-6c-3)=3c+7 | | 5(3x+8)=-14+39 | | 8-4x+8x=x-13 | | 8x-6=6x-12 | | 12m-6=32 | | x+75=x+124 | | 2x(4-3x)=2 | | 18-(c+2)=21 | | 1+2x=-6x+89 | | 7+(5x+3)=7(5x+3) | | 5=x/9+3 | | 2(x+2=10 | | 12(v+7)-4(1-2v)=v+5-4v+6 | | 3x+3=4x−8 | | 8-6k=8-k-5k | | 9x-24=4 | | -6(-3x+4)=48 | | 3.9+b/12.8=-13 |

Equations solver categories